2012
DOI: 10.3892/or.2012.1774
|View full text |Cite
|
Sign up to set email alerts
|

Impaired death-associated protein kinase-mediated survival signals in 5-fluorouracil-resistant human endometrial adenocarcinoma cells

Abstract: Abstract.A recent study showed that both 5-fluorouracil (5FU)-stimulated apoptosis and Fas-mediated apoptosis in human endometrial adenocarcinoma cells are enhanced by targeted knockdown of endogenous death-associated protein kinase (DAPK) with DAPK small-interfering RNAs. Therefore, we investigated the DAPK survival signals in three 5FU-resistant subclones. DAPK knockdown did not enhance 5FU-stimulated or Fas-mediated apoptosis in any of the three 5FU-resistant subclones, but the subclones acquired resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Moreover, it was shown that DAPK1 was capable of suppressing oncogenic transformation caused by c-Myc and E2F, which blocks the tumor metastasis [ 13 , 14 ]. DAPK1 is also mediated in anti-cancer drug resistance to 5-fluorouracil in endometrial adenocarcinoma cells [ 56 ], anti-epidermal growth factor receptor antibodies in lung cancer cells [ 57 ], gemcitabine in pancreatic cancer cells [ 58 ], and cisplatin in cervical squamous cancer cells [ 59 ].…”
Section: Dapks In Diseasementioning
confidence: 99%
“…Moreover, it was shown that DAPK1 was capable of suppressing oncogenic transformation caused by c-Myc and E2F, which blocks the tumor metastasis [ 13 , 14 ]. DAPK1 is also mediated in anti-cancer drug resistance to 5-fluorouracil in endometrial adenocarcinoma cells [ 56 ], anti-epidermal growth factor receptor antibodies in lung cancer cells [ 57 ], gemcitabine in pancreatic cancer cells [ 58 ], and cisplatin in cervical squamous cancer cells [ 59 ].…”
Section: Dapks In Diseasementioning
confidence: 99%
“…Notably, DAPK1 can modulate the resistance to some antitumor drugs. For instance, in human endometrial adenocarcinoma cells, the knockdown of DAPK1 enhances 5-fluorouracil-stimulated apoptosis and Fas-mediated apoptosis, thus enhancing the drug treatment effect . Additionally, in drug-resistant NSCLC cells, hypermethylation of DAPK1 in derivatives of epidermal growth factor receptor (EGFR) therapeutics resensitizes cells to erlotinib and cetuximab.…”
Section: The Dapk Family In Diseasesmentioning
confidence: 99%
“…For instance, in human endometrial adenocarcinoma cells, the knockdown of DAPK1 enhances 5-fluorouracil-stimulated apoptosis and Fas-mediated apoptosis, thus enhancing the drug treatment effect. 117 Additionally, in drug-resistant NSCLC cells, hypermethylation of DAPK1 in derivatives of epidermal growth factor receptor (EGFR) therapeutics resensitizes cells to erlotinib and cetuximab. Consequently, in order to increase therapeutic effectiveness and overcome anti-EGFR medication resistance, DAPK1 may therefore be a novel target.…”
Section: Dapk1 In Diseasesmentioning
confidence: 99%
“…In breast cancer MDA-MB-231 and MDA-MB-468 cells with stably expressed miR-510h, resistance to paclitaxel is significantly increased when compared to the cells transfected with vehicle vectors. After searching the global putative targets of miR-520h and sorting those associated to apoptosis, DAPK2 is picked based on its documented role as a pro-apoptotic gene [15] . MiR-520h targeting DAPK2 is verified by using Western blotting and luciferase reporter assays, respectively.…”
Section: Introductionmentioning
confidence: 99%